(untitled) (Stato, Chiese e pluralismo confessionale, 2014)
Il contributo, sottoposto a valutazione, è destinato alla pubblicazione nel volume Scientology in scholary perspective, Atti del Convegno, Antwerpen (Belgio, 24-25 gennaio 2014), a cura di R. Dericquebourg,Equinox Publishing. SUMMARY: 1. Preliminary observations. The recent English case law about Scientology - 2. The long Italian process - 3. The condemnation of the religious movement in France - 4. Conclusion.